Análise comparativa do tratamento do condiloma acuminado anal e perianal utilizando plasma de argônio e eletrofulguração em doentes HIV positivo e negativo - Braga, Eduardo Angelo [UNIFESP] (2017)
Introduction: Human papillomavirus (HPV) infection is the sexually transmitted disease most frequently diagnosed in Brazil, in both men and women and its incidence has been increasing over recent years. It may occur in association with the human immunodeficiency virus (HIV) in up to 62% of the cases1,2. Despite various forms of treatment for Condylomata, relapses are frequent and both the immediate and the long-term results are unsatisfactory. Use of argon plasma is an attractive option because its results are effective. However, further studies comparing this with the standard treatment are still needed. Purpose: To compare the efficiency and complications of treatments for anal and perianal condyloma using argon plasma and electrofulguration and the recurrence rates of these treatments. Methods: From January 2013 to April 2014, in 37 cases of perianal and anal condyloma, the patients’ anal region was divided into two semicircles. Treatment with argon plasma coagulation or electrofulguration was then randomly assigned (one method for each semicircle). The therapeutic sessions were repeated until clinical signs of HPV infection had been eliminated. Tissue samples were taken for cytological, histological and PCR evaluations. Results: The HPV genotype, presence of more than one genotype per patient, oncological potential per genotype and cytological and histological results were analyzed. There was no significant difference in effectiveness between the argon and fulguration methods, based on recurrence and disease-free interval (p > 0.05). In relation to argon application, the variables studied were not associated with recurrence of condyloma (p > 0.05). However, the areas treated with electrofulguration in HIV-positive patients presented more relapses, with a significant difference (p = 0.01). Conclusion: Use of argon plasma was less influenced by presence of HIV than was use of electrofulguration. With regard to efficacy, the methods were statistically equivalent, however, the areas treated with electrofulguration in HIV-positive patients presented worse results with more relapses.